Associations of physical activity with quality of life and sleep quality among adults with hypertension in primary care - Iba Supra Saba; Sumbara Sumbara (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Hypertension is a major public health problem that negatively affects patients' quality of life and sleep quality. Physical activity is an important non-pharmacological strategy that may improve both outcomes; however, evidence from primary healthcare settings remains limited. Purpose: To examine the relationship between physical activity, quality of life, and sleep quality among patients with hypertension. Method: This analytical correlational study employed a cross-sectional design involving 84 hypertensive patients selected from a population of 352 registered at Singajaya Public Health Center. Data were collected using a respondent characteristics questionnaire, the Global Physical Activity Questionnaire (GPAQ), the World Health Organization Quality of Life-BREF (WHOQOL-BREF), and the Pittsburgh Sleep Quality Index (PSQI). Descriptive statistics and Spearman's rank correlation test were used for data analysis, with a significance level of 0.05. Results: Most participants had low physical activity (38.1%), good quality of life (54.8%), and poor sleep quality (52.4%). Physical activity was positively correlated with quality of life (ρ = 0.721, p < 0.001) and negatively correlated with PSQI scores (ρ = -0.628, p < 0.001), indicating that higher physical activity was associated with better quality of life and better sleep quality. Conclusion: Higher levels of physical activity were significantly associated with better quality of life and sleep quality among patients with hypertension. These findings support the importance of promoting physical activity as part of hypertension management in primary healthcare settings. Keywords: Hypertension; Physical Activity; Quality of Life; Sleep Quality; Primary Healthcare.